BA 215 - Survey of Accounting - Linn Benton Virtual College (2018)
This course introduces financial accounting techniques, measuring and recording transactions, preparing financial statements, managerial decision making, and planning and control devices, such as budgeting, cost accounting, variance analysis, and break-even analysis. Includes assessment of financial information from managers, lenders, and investors perspective to understand and evaluate business operations. Emphasizes ethical decision-making in the work environment.